Long-Acting Injectable naltrexone for the Management of patients with Opioid Dependence - Kimberly L. Kjome; F. Gerard Moeller (SAGE Publishing, 2011)
Opioid dependence is a condition with serious clinical ramifications. Treatment has focused on detoxification, agonist therapy with methadone or buprenorphine, or remission maintenance with the opioid antagonist, naltrexone. Treatment with oral naltrexone has been limited by poor treatment adherence and relapse. Studies with long-acting formulations have shown increased treatment adherence. Extended-release injectable naltrexone has been used for the treatment of alcohol dependence, and has recently received an indication for treatment of opioid dependence from the US Food and Drug Administration. Dosing occurs once monthly and existing data with long-acting naltrexone supports efficacy of treatment for opioid dependence; however published data is sparse. Treatment with long-acting naltrexone should be monitored for hepatotoxicity, and patients should be made aware of increased risk of overdose with administration of opioids during and immediately after discontinuation of long-acting naltrexone.